Gender in Education: A Challenge for All... - De León Quintana, Beysi (2009)
All over the world, a good education is the key to building a better future as it helps individuals to fully realize themselves. Isn't this, perhaps, the goal of education? If we take this premise as a basis, this essay aims to create in the reader a moment of critical reflection on the way in which the educational experience develops, from a gender perspective in the classroom, and how this situation influences, day by day, society as a whole. Likewise, this is a clear invitation to teachers to break with those rigid dynamics present in the management of classes, which have allowed the consolidation of stereotypes that are opposed to the socio-educational advances that the country requires.